1969
DOI: 10.1530/jrf.0.0190255
|View full text |Cite
|
Sign up to set email alerts
|

Embryo Mortality in the Heat Stressed Ewe

Abstract: Continuous hot-room exposure during the first 15 days of pregnancy raised the rectal temperatures and respiratory rates of mature Merino ewes to about 104 to 105\s=deg\F and 170 respirations/min respectively and led to the death of 83% of embryos.Similar ewes subjected to a diurnally variable heat stress, which raised their rectal temperatures and respiratory rates to about 104 to 105\s=deg\F and 220 respirations/min during an 8-hr 'day' and allowed them to fall to about 102\s=deg\F and 140 respirations/min re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

1970
1970
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…Similarly, in Exp. 100 C. J. Thwaites The relative numbers of lutein cell types and the proportion of lutein cells in the cl did not differ significantly between groups (Thwaites, 1968a) and group mean values ( + S.E.) It was, however, associated with a reduction in embryo size (Table 4) and, for embryo weight, this reduction approached significance.…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations
“…Similarly, in Exp. 100 C. J. Thwaites The relative numbers of lutein cell types and the proportion of lutein cells in the cl did not differ significantly between groups (Thwaites, 1968a) and group mean values ( + S.E.) It was, however, associated with a reduction in embryo size (Table 4) and, for embryo weight, this reduction approached significance.…”
Section: Resultsmentioning
confidence: 85%
“…Full details of conditions experienced by ewes in the various experiments have been reported elsewhere (Thwaites, 1968a(Thwaites, , b, 1969, it is sufficient to record here that prevailing temperatures ranged from 33°to 72°F and that mean hot-room temperatures in different experiments varied between 96·5°and 100°F with approximately 50% relative humidity. Full details of conditions experienced by ewes in the various experiments have been reported elsewhere (Thwaites, 1968a(Thwaites, , b, 1969, it is sufficient to record here that prevailing temperatures ranged from 33°to 72°F and that mean hot-room temperatures in different experiments varied between 96·5°and 100°F with approximately 50% relative humidity.…”
Section: Methodsmentioning
confidence: 86%
See 2 more Smart Citations
“…Thwaites (1969) has reviewed the results of a number of hot room studies which have demonstrated that ewes subjected to continuous heat stress during mating and early pregnancy suffer high levels of fertilisation failure and embryonic mortality. The relevance of these studies to the field situation is somewhat doubtful, since it appears clear that the diurnally variable component of natural heat stress has an ameliorating effect on fertilisation failure and embryonic mortality (Thwaites 1969).…”
Section: Dsscussionmentioning
confidence: 99%